2005
DOI: 10.1097/01.brs.0000167827.84020.49
|View full text |Cite
|
Sign up to set email alerts
|

Constructs Incorporating Intralaminar C2 Screws Provide Rigid Stability for Atlantoaxial Fixation

Abstract: The results clearly indicate the potential of the intralaminar screw technique to provide stability that is equivalent to methods currently used. Given the serious complications that can follow vertebral artery injury and the decreased likelihood of injury by avoiding placement of C2 pedicle screw(s) and C1-C2 transarticular screw(s), strong consideration should be given to using a construct that incorporates C2 intralaminar screw(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(74 citation statements)
references
References 19 publications
2
71
0
1
Order By: Relevance
“…With at least 0.5 mm tolerance bilaterally, a pedicle or laminar screw of 3.5-mm diameter can be placed safely by experienced hands. Furthermore, a trajectory of laminar screw placement with slight penetration of the dorsal cortex had been recommended by several authors [2,7]. For a patient with a relatively thin C2 laminar, this method has the benefit of placement with great ease, without the concern of penetration into the spinal canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With at least 0.5 mm tolerance bilaterally, a pedicle or laminar screw of 3.5-mm diameter can be placed safely by experienced hands. Furthermore, a trajectory of laminar screw placement with slight penetration of the dorsal cortex had been recommended by several authors [2,7]. For a patient with a relatively thin C2 laminar, this method has the benefit of placement with great ease, without the concern of penetration into the spinal canal.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Wright et al [19] reported a new technique involving bilateral C2 laminar screws, which reduces the threat to the vertebral artery. Biomechanically, the intralaminar screw constructs were shown to provide equivalent stability to the pedicle screw constructs [7]. Similarly, Lapsiwala et al [10] also found that C2 translaminar screws provide equal structural stiffness as compared with transarticular screws and C2 pedicle screws.…”
Section: Introductionmentioning
confidence: 96%
“…Biomechanical stability of this fixation technique has recently been evaluated by Gorek et al [12], who found intralaminar screw constructs to be biomechanically equivalent to the Harms construct, and by extrapolation to the Magerl-Gallie construct for atlantoaxial fixation. In a similar study, Lapsiwala et al [13] have reported on a cadaveric biomechanical study comparing intralaminar to pedicle and transarticular screws for C1-C2 fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to transarticular screw (Jeanneret and Magerl) [9] and pedicle screw techniques, this method can provide similar stability to the atlantoaxial complex [5,12,13], which is considered to be simpler and safer due to the less intraoperative exposure and minimal risk of vertebral artery injury [2,3,8,15,24]. Subsequent morphological studies reported the applicability of this technique in different populations and showed that this method could be applied safely in most of the specimens they studied [2,7,11,19,22].…”
Section: Introductionmentioning
confidence: 99%